Wschodni model współczesnego wychowania państwowego na przykładzie rosyjskiego korpusu kadetów. Zarys problemu - Jastrzębski, Przemysław (Biuletyn Historii Wychowania, 2012)
The modern model of state education in Russia promotes patriotism and devotion to the authorities. Young people must be proud of their origin and, in spite of deteriorating material conditions, should stay in the country contributing to its development. Cadet Corps Alumni are an example of a patriotic education model. Several years of learning in the military school shapes their beliefs and teaches them complete surrender to authority. Patriotism, combined with the sense of external threat, has become the driving force behind the reconstruction of the Russian superpower. One of the cornerstones of the school is the acceptance of Putin’s Russia by spreading the vision of becoming an international representative of the country. The increase in military spending and functioning of military schools such as the Corps of Cadets give rise to fears that in the future Russia the army will become one of the tools of the superpower on the arena of foreign policy.